RELIGION AS INSRUMENT OF SOCIALIAZATION AND SOCIAL CONTROL - Okon, Etim E . (European Scientific Journal, ESJ, 2012)
Sociologists for many years have identified the family, the school, the peer group, the mass media and political movements as agents of socialization. Majority of sociologists do not consider religion as a potent agent of socialization. The conservative roles of religion in perpetuating social and cultural values are often ignored. This paper seeks to correct such mistake and to present religion as a veritable platform for socialization and social control. The study reveals that religion exercises a pervasive influence on all other social institutions thereby moderating the activities of the above-mentioned agents of socialization.